2015
DOI: 10.1159/000437154
|View full text |Cite
|
Sign up to set email alerts
|

Die Anwendung von <b><i>Bryophyllum pinnatum</i></b>-Präparaten in der Geburtshilfe und Gynäkologie - eine multizentrische prospektive Beobachtungsstudie

Abstract: Hintergrund:Bryophyllum pinnatum wurde durch die anthroposophische Medizin in Europa eingeführt und wird heutzutage auch in der konventionellen Medizin breit angewendet. Ziel dieser Studie war es, die Verordnungen im Bereich Gynäkologie und Geburtshilfe in der Schweiz sowie das Wirkungspotenzial von B. pinnatum und mögliche unerwünschte Ereignisse zu erfassen. Patienten und Methoden: Arztpraxen und Kliniken für Geburtshilfe und Gynäkologie wurden gebeten, die Verordnungen von B. pinnatum bei ihren Patientinnen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Very recently, an online survey in Switzerland showed that in gynecology and obstetrics, B. pinnatum (50% tablets) is being prescribed for pregnant women in the case of premature labor, and against restlessness and hyperactive bladder. With twothirds of the patients being treated at the University Hospital of Zurich, this work showed that B. pinnatum is a herbal product whose use is no longer confined to the AM, but has been integrated in conventional settings [65].…”
Section: Preparations and Applicationmentioning
confidence: 95%
“…Very recently, an online survey in Switzerland showed that in gynecology and obstetrics, B. pinnatum (50% tablets) is being prescribed for pregnant women in the case of premature labor, and against restlessness and hyperactive bladder. With twothirds of the patients being treated at the University Hospital of Zurich, this work showed that B. pinnatum is a herbal product whose use is no longer confined to the AM, but has been integrated in conventional settings [65].…”
Section: Preparations and Applicationmentioning
confidence: 95%
“…Retrospective analyses revealed good effectiveness and very good tolerability in patients treated with B. pinnatum preparations [8,9] and a matched-pairs study corroborated these results [10]. More recently, an observational study was performed [11]. The use of B. pinnatum as a tocolytic agent is supported by experimental evidence [12].…”
Section: Introductionmentioning
confidence: 93%
“…Flavonoids are major metabolites in B. pinnatum, and include numerous flavonol derivatives (9-30), in particular, quercetin and kaempferol glycosides, and some flavones (31)(32)(33)(34)(35) (Figure 2) [7,[12][13][14][15][16][17][18][19][20][21][22].…”
Section: Phytochemistry Of B Pinnatummentioning
confidence: 99%
“…A recent online survey in Switzerland showed that in gynecology and obstetrics, "Bryophyllum chewable tablets" are being prescribed for pregnant women in the case of premature labor, and against restlessness and hyperactive bladder. With twothirds of the patients being treated at the University Hospital of Zurich, this survey showed that B. pinnatum is an herbal product which is no longer confined to anthroposophic medicine, and is meanwhile also used in conventional settings [33].…”
Section: Bryophyllum Preparations and Clinical Usesmentioning
confidence: 99%